IMMUNOLOGY OF TUBERCULOSIS - Federica Bozzano; Francesco Marras; Andrea De Maria (Mediterranean Journal of Hematology and Infectious Diseases)
MTB ranks as the first worldwide pathogen latently infecting one third of the population and the second leading cause of death from a single infectious agent, after the human immunodeficiency virus (HIV). The development of vigorous and apparently appropriate immune response upon infection with M.tuberculosis in humans and experimental animals conflict with failure to eradicate the pathogen itself and with its ability to undergo clinical latency from which it may exit. From a clinical standpoint, our views on MTB infection may take advantage from updating the overall perspective, that has quite changed over the last decade, following remarkable advances in our understanding of the manipulation of the immune system by M.tuberculosis and of the role of innate components of the immune response, including macrophages, neutrophils, dendritic cells and NK cells in the initial spread of MTB and in its exit from latency. Scope of this review is to highlight the the major mechanisms of MTB escape from immune control and to provide a supplementary translational perspective for the interpretation of innate immune mechanisms with particular impact on clinical aspects.